Clustered cardiovascular disease risk among children aged 8–13 years from lower socioeconomic schools in Gqeberha, South Africa. Issue 2 (24th June 2022) - Dolley, Danielle; Walter, Cheryl; du Randt, Rosa; Pühse, Uwe; Bosma, Jacob; Aerts, Ann; Adams, Larissa; Arnaiz, Patricia; Degen, Jan; Gall, Stefanie; Joubert, Nandi; Müller, Ivan; et al.
Abstract : Objectives: To determine the prevalence of individual cardiovascular disease (CVD) risk factors and clustered CVD risk among children attending schools in periurban areas of Gqeberha and to investigate the independent association between clustered CVD risk, moderate to vigorous physical activity (MVPA) and cardiorespiratory fitness (CRF). Methods: Baseline data were collected in a cross-sectional analysis of 975 children aged 8–13 years. We measured the height, weight, waist circumference, blood pressure, fasting glucose, full lipid panel, 20 m shuttle run performance and accelerometry. The prevalence of individual risk factors was determined, and a clustered risk score (CRS) was constructed using principal component analysis. Children with an elevated CRS of 1 SD above the average CRS were considered 'at-risk'. Results: We found 424 children (43.3%) having at least one elevated CVD risk factor: 27.7% elevated triglycerides, 20.7% depressed high-density lipoprotein cholesterol and 15.9% elevated total cholesterol. An elevated clustered risk was identified in 17% (n=104) of the sample; girls exhibited a significantly higher CRS >1 SD than boys (p=0.036). The estimated odds of an elevated clustered risk are doubled every 2 mL/kg/min decrease in VO2 max (95% CI 1.66 to 3.12) or every 49 min reduction in MVPA (95% CI 27 to 224). Conclusion: A relatively high prevalence of elevated individual and clustered CVD risk was identified. Our results have also confirmed the independent inverse association of the clustered CVD risk with physical activity and CRF. These indicate that increased levels of CRF or MVPA may aid in the prevention and reduction of elevated clustered CVD risk.